EFL Students’ Perception of the Effectiveness of Blended Learning Environment in Higher Education - Daniel Pakiding; Syarifah Farahdiba; Muhammad Miftah Fauzan (Journal of Excellence in English Language Education, 2026)
This study aimed to discover EFL Students’ Perception of The Effectiveness of Blended Learning Environments in Higher Education. The researcher applied a descriptive qualitative method to achieve the research objective. The data were collected through semi-structured interviews. The subjects of the research were ten English Education Study Program students at the Faculty of Languages and Literature, Universitas Negeri Makassar. The subjects were chosen by using a random sampling technique. Based on the results of the study, the students perceived that the blended learning environment in higher education is still considered less effective in supporting their learning process. There are several reasons why they concluded that the blended learning environment is still less effective. Some of the reasons include a lack of classrooms, online learning websites that often crash, and inconsistent class scheduling. The findings imply that a variety of factors, such as teaching methodology, institutional support, and technological usability, influence students' opinions of blended learning. This study emphasizes the necessity for universities to guarantee dependable infrastructure and inclusive learning environments, as well as for instructors to enhance online involvement.